2004
DOI: 10.3758/bf03195003
|View full text |Cite
|
Sign up to set email alerts
|

Serial processing in melody identification and the organization of musical semantic memory

Abstract: Unlike the visual stimuli used in most object identification experiments, melodies are organized temporally rather than spatially. Therefore, they may be particularly sensitive to manipulations of the order in which information is revealed. Two experiments examined whether the initial elements of a melody are differentially important for identification. Initial exposures to impoverished versions of a melody significantly decreased subsequent identification, especially when the early exposures did not include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
19
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 45 publications
7
19
0
Order By: Relevance
“…However, identification performance was relatively flat through the 1-5-9, 2-6-10, and 3-7-11 conditions, so it would be difficult to argue that there was a strong relationship between similarity and identification performance. The confusion error data matched those observed in previous work in that approximately half of the errors were of one of two types (Schulkind, 2004). Genre errors were numerous, but are difficult to interpret because only a small number of genres were used in the experiment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, identification performance was relatively flat through the 1-5-9, 2-6-10, and 3-7-11 conditions, so it would be difficult to argue that there was a strong relationship between similarity and identification performance. The confusion error data matched those observed in previous work in that approximately half of the errors were of one of two types (Schulkind, 2004). Genre errors were numerous, but are difficult to interpret because only a small number of genres were used in the experiment.…”
Section: Discussionsupporting
confidence: 77%
“…Only melodies that are musically similar to the target initially enter (access) and subsequently remain (selection) in the active cohort. Data reported by Schulkind (2004) bear on the similarity hypothesis. He found that confusion errors -misidentifying a target melody as a different song -were relatively rare (< 10% trials) and that the majority of errors bore no musical similarity to the target.…”
mentioning
confidence: 88%
“…People can process tunes on the basis of musical qualities, as well, such as key, rhythm, and so forth (see, e.g., Halpern, 1984b;Schulkind, 2004). Nonetheless, the ease with which people treat familiar songs on the basis of conceptual similarities (Halpern, 1984a) and the priming based on these conceptual similarities, as shown here, present strong evidence that meaning may dominate both the organization of familiar music and the functionality of memory for music.…”
Section: Discussionmentioning
confidence: 64%
“…Other evidence strengthens this general conclusion; for example, Schulkind (2004) noted a high rate of genre confusions in his study of identification of familiar melodies. These thematic-based errors were nearly as common as phrasing/meter errors, although the latter were substantially more relevant to the participants' task.…”
mentioning
confidence: 75%
See 1 more Smart Citation